Mitomycin C inhibits mouse parthenogenic embryo development in preimplantation stage - Long, Le Thanh; Son, Hoang Nghia; Dam, Nguyen Van; Thuong Huyen, Nguyen Thi (Academia Journal of Biology, 2012)
To investigate effects of Mitomycin C on mouse parthenogenic embryo in vitro development, we exmanined mouse parthenogenic in vitro development treated by Mitomycin C. Matured oocytes collected from oviduct were treated in KSOM medium supplemented Mitomycin C 10 mg/ml for 0.5, 1, 2 hours and KSOM medium supplemented Mitomycin C 10, 20, 30, 40 and 50 mg/ml for 2 hours. Results demonstrated that Mitomycin C degraded parthenogenic embryo in vitro development from all groups. Most of embryos could not reach to blastocyst stage and prevented by first block on developing from 2-cell embryo stage to 4-cell embryo stage. 4-cell embryo development rates following Mitomycin C treatment times of 0.5, 1, 2 hours were 30.15%, 25.42% and 8.33%, all of them were lower than control group (70.96%). 4-cell embryo development rates following Mitomycin C treatment concenstrations of 10 mg/ml  (8.33%), 20 mg/ml (6.56%), 30 mg/ml (6.06), 40 mg/ml  (3.85) and 50 mg/ml (0%) were very low, especially no embryo could reached to 4-cell embryo stage in 50 mg/ml group. In the other hand, Mitomycin C elongated the time of cell division from one-cell embryo stage to 2-cell embryo stage. All most Mitomycin C treated embryos divided into 2-cell embryo after 48 hours but in control group, parthenogenic embryo divided after 24 hours. This result showed that Mitomycin C not only effects on DNA but also effects on some proteins concerning to cell division. Blocked embryos showed apoptotic morphologies such as cytoplasm fragment, chromatin condensation and nucleus fragment. Mitomycin C also produced abnormalities of chromosome division in embryos. DAPI - stained embryos showed that number of dividing chromosome were not unequal in mitosis. In control group, Mitomycin C - untreated mouse parthenogenic embryos could reach to blastocyst and had normal morphologies of cytoplasm and nucleus. Thus, Mitomycin C degraded mouse parthenogenic in vitro development in preimplantation, produced abnormalities and drived embryos to apoptosis.